Kajian Eksegesis Terhadap Efesus 2:11-22 Guna Mengevaluasi Eksklusivitas Yahudi - Sakey, Jenet Selfiani; Tampilang, Petra Harys Alfredo; Pamilangan, Daniel (STT Pelita Dunia, 2025)
This study aims to evaluate the concept of Jewish exclusivity through an exegesis of Ephesians 2:11–22. By examining the historical context, rhetorical structure, and key terms in the text, this study shows how Paul interprets Christ's work of reconciliation as an act that definitively breaks down the cultic and ethnic barriers between Jews and non-Jews. Exegetical analysis reveals that the identity of God's people is no longer determined by lineage or the privileges of the Law, but rather by participation in the work of Christ's cross, which creates “one new humanity.” This finding confirms that Ephesians 2:11–22 not only rejects Jewish claims of exclusivity, but also offers a theological framework that replaces ethnic privilege with a communal identity rooted in Christ, thereby reaffirming the universal nature of the new covenant people.